THE ROLES OF EDUCATOR IN DISRUPTIVE ERA - Erfiati Erfiati; Lailatussaadah Lailatussaadah (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2022)
This study aims at exploring the roles of educators in conducting teaching learning activity during disruptive era. The method used in this study was the Literature Review by searching articles on electronic journals database. The database used in this study were Google Scholars, Springer and Science Direct from 2003 to 2018. 10 articels were found using keyword: The roles of educator, teaching and learning activities and disruptive era. The data were analized by collecting the related articles, reducing it based on the discussion topic, displaying the data and last but not the least, taking the conclusion. The result of this study found that the shifting of educational paradigm requires the adoption of the roles of educators in conducting teaching learning process in disruptive era.  In terms of the role of educators, there are some shifting of the role of educators in the disruptive era; the role of educators as conceptor, innovator, facilitator and innovator/ role model. This study describes some phenomenon of educational paradigm and the roles of educators in Indonesia. It is urged that further study on this issue is carried out in more global context.